Modes of interactions between environmental drivers and marine biota - Boyd, Philip W.; Brown, Christopher J. (Frontiers in Marine Science, 2015)
The responses of marine biota to global ocean change is characterised by multiple environmental drivers that interact to cause non-linear changes in organismal performance. Characterising interactions is critical for us to predict whether multiple drivers will accelerate or mitigate future biological responses. There is now a large body of evidence that drivers do not act independently, a common null model, but rather have synergistic or antagonistic effects on organisms. We review the literature on interactions among environmental drivers such as ocean acidification and warming, and identify three common modes of interaction: physicochemical interactions in the seawater media outside organisms, interactions that operate on organisms directly, for example by altering physiological rates; and interactions that occur through changes in ecosystems, like predation. Interactions can also occur across these levels increasing the number of permutations for interaction, and point to a diverse range of modes of interplay. Identifying the appropriate mode will help generalise interaction types to unstudied contexts.